Production of low-salt restructured Mediterranean horse mackerel (Trachurus mediterraneus) using microbial transglutaminase/caseinate system - TZIKAS (Ζ. ΤΖΗΚΑΣ), Z.; SOULTOS (Ν. ΣΟΥΛΤΟΣ), N.; AMBROSIADIS (Ι. ΑΜΒΡΟΣΙΑΔΗΣ), I.; LAZARIDOU (Α. ΛΑΖΑΡΙΔΟΥ), A.; GEORGAKIS (ΣΠ. ΓΕΩΡΓΑΚΗΣ), SP. (Journal of the Hellenic Veterinary Medical Society, 2018)
Low-salt restructured fish products without cooking were prepared from Mediterranean horse mackerel using varying levels of NaCl (0-control, 10 and 20 g/Kg) and microbial transglutaminase (MTG) (0-control, 5 and 10 g/Kg). Restructured products with the highest textural strength and sensory acceptability were obtained at 1% MTG and 2% NaCl. The use of MTG made the low salt (1%) product comparable to one prepared with 2% NaCl only. WHC was not affected by MTG at 0% NaCl. The microbiological analysis (Total Viable Bacteria, Shewanella putrefaciens, Pseudomonas spp. and Enterobacteriaceae) suggests a relatively short shelf-life (< 4 days) at refrigeration temperature (2±2ºC). The cooked restructured products received more favourable scores with increased levels of MTG and NaCl.